Pembangunan Ekonomi Dan Masa Depan Demokrasi Di Indonesia Studi Kebijakan Ekonomi-Politik Antara Tahun 1985-1997)The Economic Development and Democratic Prospects inIndonesia (A Study on Political Economic - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT Since coming into being and despite ever giving a good prospects of democracy, the New Order Government has strived hard for its political life security and that it has done a variety of regulations in both economy and politics. In the sameway, the goverment has intervened much in many different economic and social political activities. Taking the argumentation of Lipset's (1963) and Liddle's (1993) it would be very interesting for us to study the relevance between the economic achievement of New Order government together with its crises and the prospects of democracy in Indonesia. Different from that found in western countries, the economic development has apparently brought Indonesia to authocratic government, and that the economic crises has often availed the process of democracy. The study shows that the economic achievement has not given a strong foundation to the development of democratic system. Therefore, despite the demand of economic liberalization in responding to the crises happening in the middle of the 1980s, and that all their rehabilitation and transparency in both economic and political programs, the government still shows its authocratic attitude. In the government running, there have been many irragularities in the form of policy distortions in both politics and economy and that has resulted in mismanagement and stagnation in the political system. Besides having worsened the monetary crises in 1997, this fact has raised such other forms of crises and then brought the regime of New Order to collapse. It is the right moment to encourage a better democratic life. But as we soon learn that due 1. Universitas Muhammadiyah, Ponorogo 2. Fakultas timu Sosial dan limu Politik Universitas Gadjah Mada, Yogyakarta.